Business Design And Implementation Of Pricing Strategies To Maintain The Frozen Food Business - Dinar Cahya Wancirina; Erlita Ridanasti (International Journal of Economics, Business and Innovation Research, 2024)
Dinni.eats is a culinary business focused on the frozen food industry, catering to changing lifestyles and preferences for ready-to-eat food. The high levels of busyness and limited time encourage the need for simple, practical, yet nutritious options. The frozen food market in Indonesia is growing significantly, presenting vast opportunities. Dinni.eats offers products with an emphasis on shelf life, safe packaging, and practicality. Initially, the business faced challenges with rising chicken prices, prompting a low-cost strategy to maintain affordability. At the beginning of its business journey, Dinni.eats faced the problem of rising prices for chicken raw materials, so the owner was concerned that the selling price would not increase. To deal with this, the owner of Dinni.eats tries to use a low cost strategy so that selling prices remain affordable for customers. Apart from that, Dinni.eats also offers a variety of dishes using fish as raw ingredients. Additionally, Dinni.eats diversified its offerings with fish-based dishes like Tongkol Sambalado and Ungkep Fish to stabilize sales and prevent decline.